Trade and economic cooperation between Kazakhstan and Russia: features and development priorities - A. M. Myrzakhmetova; D. U. Alshimbayeva; K. A. Turkeeva; A. T. Yerimpasheva (Экономика: стратегия и практика, 2020)
The purpose of the article is to identify the features and substantiate new priorities of the development of trade, economic and investment cooperation between two countries in modern conditions. Methods of economic, statistical, comparative, graphic, systemic, functional and other methods of analysis are applied. In the course of the study, new directions and approaches were developed for the eff development of trade and economic cooperation between two countries and the implementation of an adequate foreign trade policy of Russia and Kazakhstan. The main approach is to expand regional trade through the mechanism of participation in the Eurasian Union, the intensifi of corporate ties through the creation of joint ventures, based on the use of advanced scientifi technologies to increase the production of competitive products. The presented article reveals the current state of trade, economic and investment cooperation between Kazakhstan and Russia in the context of the growing processes of globalization and regionalization. In these conditions, competition is getting tougher in the world market, which objectively predetermines the need to combine eff of interconnected and interdependent national economies of Kazakhstan and Russia. In order to achieve this goal the following tasks were solved: the content was disclosed, and the main directions of trade, economic, investment interaction between the two countries were determined; revealed and disclosed the features of the development of trade and economic cooperation between the two countries in modern conditions; proposals for the eff development of trade, economic and investment cooperation between Kazakhstan and Russia have been developed in the context of the growing crisis processes associated with the coronavirus pandemic.